Manejo da adubação com esterco bovino na cultura do rabanete (Raphanus sativus L.) - Marcatto, Giovanni Zonato (Universidade Federal de São Carlos, 2021)
The use of bovine manure as an alternative to mineral fertilization can reduce production costs, reduce the need for irrigation, provide an appropriate destination for manure produced by cattle farming and better soil conditioning, in addition to allowing the product to be certified organic for various crops, including the radish crop. This work aimed evaluate the effect of fertilizing with tanned manure on radish productivity and quality. The experiment was conducted in two trials, the first in 20-liter pots, with six treatments of inclusion of bovine manure at doses of 0, 30, 60, 90, 120, 150 t.ha-1 in sandy and clayey soil condition , and the second in field with 0, 20, 40, 60, 80 and 100 t.ha-1 of incorporated tanned bovine manure. At the time of harvest, the dry matter weight of roots (radishes), the length and diameter of the roots, as well as leaf area and rate of radishes with commercial potential were evaluated. In clay soil cultivation, organic fertilization with bovine manure, regardless of the applied dose, was positive for the cultivation of radish, in terms of greater root and leaf biomass and radish diameter. On the other hand, in the cultivation in sandy soil, the application of manure does not seem to have positively interfered in the production of root and leaf biomass, regardless of the applied dose. In addition, with fertilization, a higher rate of radishes showed commercial potential.
Management of bovine manure in radish (Raphanus sativus L.)
Keywords: Agricultura familiar; Hortaliça; Horticultura; Family farming; Horticulture; Greenery; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA